An AHP-ISM approach for considering public preferences in a public transport development decision - Duleba, Szabolcs (Transport, 2019)
Recently, there has been a transparent need to involve public in transport development decisions not only in the EU but also in other countries worldwide. Public involvement in decision-making, however, suffers from two critical issues: lack of expertise and lack of enthusiasm. This paper aims to overcome the first problem: how to amend passenger preferences related to public transport development with expert knowledge on transport systems. For this purpose, a new research methodology has been created which combines the well proven Analytic Hierarchy Process (AHP) and Interpretive Structural Modelling (ISM) methods in a novel way. ISM is used to reveal the non-hierarchical connections of the transport system elements and by this, AHP results are modified with the consideration of element interactions. The first stage of the three-stage-survey has been conducted in Yurihonjo (Japan), the second and third in an international workshop with the participation of experts. Results show that the original AHP scores – gained from passenger evaluations – are significantly modified by adding expert knowledge on factor interactions, thus new preference order is gained related to the importance of the development of public transport system elements. The introduced procedure can be applied for other public transport system improvement decision-making situations in which passenger involvement is required. First published online 18 March 2019